2007
DOI: 10.1159/000103001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Degree of Malnutrition and Echocardiographic Parameters in Hemodialysis Patients

Abstract: Background: The aim of this study is to investigate the relationship between the degree of malnutrition and inadequate volume control evidenced by echocardiography. Methods: In this study 72 chronic hemodialysis patients were investigated in a cross-sectional manner. The malnutrition score was calculated using Subjective Global Assessment. M-mode echocardiography was performed in all patients. Results: The highest malnutrition score (23.2 ± 1.5 points) and lowest vena cava inferior collapse index (35 ± 2%) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…In addition to these traditional risk factors, patients with CKD may have other risk factors for increase cardiovascular risk such as inflammation, oxidative stress, anemia, metabolic disorders, calcium-phosphorous disorders, hypervolemia, and structural and functional abnormalities of heart, which may help to explain the high cardiovascular morbidity and mortality in such patients [2025]. LVH, a common finding in patients with CKD, has been reported to advance with decreases in glomerular filtration rate [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these traditional risk factors, patients with CKD may have other risk factors for increase cardiovascular risk such as inflammation, oxidative stress, anemia, metabolic disorders, calcium-phosphorous disorders, hypervolemia, and structural and functional abnormalities of heart, which may help to explain the high cardiovascular morbidity and mortality in such patients [2025]. LVH, a common finding in patients with CKD, has been reported to advance with decreases in glomerular filtration rate [3].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition may worsen the outcome of CKD by aggravating existing inflammation and heart failure [27]. Hypoalbuminemia has been correlated with left ventricular structure and function [25, 28, 29]. Kursat et al [25], evaluating the relationship between the degree of malnutrition and echocardiographic parameters in 72 hemodialysis patients, found that the malnutrition index, calculated using Subjective Global Assessment, had a positive correlation with left ventricular mass and index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid overload may be involved in the pathogenesis of malnutrition 21. Previous reports had observed an independent relationship between malnutrition and extracellular fluid volume overload in dialysis patients 10, 22. The mechanisms to explain the correlation between fluid status and nutritional status remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…In report by Kursat et al, they found the malnutrition index, calculated using Subjective Global Assessment, had a positive correlation with LA diameter (LAD) 10. They explained their findings by inadequate volume control.…”
Section: Introductionmentioning
confidence: 96%